2014
DOI: 10.1016/j.euromechflu.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The lift-up effect: The linear mechanism behind transition and turbulence in shear flows

Abstract: The formation and amplification of streamwise velocity perturbations induced by cross-stream disturbances is ubiquitous in shear flows. This disturbance growth mechanism, so neatly identified by Ellingsen and Palm in 1975, is a key process in transition to turbulence and self-sustained turbulence. In this review, we first present the original derivation and early studies and then discuss the non-modal growth of streaks, the result of the lift-up process, in transitional and turbulent shear flows. In the second… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
127
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(134 citation statements)
references
References 123 publications
(167 reference statements)
7
127
0
Order By: Relevance
“…To determine the instability mechanism in our flow, we note that the present instability is stationary, the mode shape streamwise elongated, and the streamwise velocity component order of magnitude larger than the vertical component ( figure 4 a and b). This strongly indicates a lift-up mechanism, where a small initial v-perturbation induces a strong u-perturbation (for a review on lift-up see Brandt (2014)). …”
Section: Linear Stability Analysismentioning
confidence: 99%
“…To determine the instability mechanism in our flow, we note that the present instability is stationary, the mode shape streamwise elongated, and the streamwise velocity component order of magnitude larger than the vertical component ( figure 4 a and b). This strongly indicates a lift-up mechanism, where a small initial v-perturbation induces a strong u-perturbation (for a review on lift-up see Brandt (2014)). …”
Section: Linear Stability Analysismentioning
confidence: 99%
“…This transient growth is related to inviscid instabilities whereby shear flows can be unstable to disturbances in the cross-stream velocity components, whose kinetic energy grows linearly in time, even though the base flow does not contain any inflection point. 11,12 For the particular case of round jets, recent works on non-modal instability 13,14 have shown that transient growth of helical perturbations (azimuthal wavenumber m = 1) is favored by this algebraic instability, due mainly to the lift-up effect, 11,12,15 although the Orr mechanism, 16 i.e., the progressive vortex sheet alignment with shear, has been also proven to occur in jets subjected to optimal harmonic forcing. 17 In an attempt to unravel the role of different transient mechanisms in round jets, Jiménez-González et al 18 have recently identified two mechanisms, within the framework of a parametric study aiming at analyzing the influence of the jet velocity profile on the instability of axisymmetric (m = 0) and helical (m = 1) perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…If the transient amplification of kinetic energy for axially invariant perturbations is sufficiently large, in view of previous results on shear flows, 15 it could be conjectured that a nonlinear transition may be eventually triggered in the jet, when the perturbation is initially injected, which might be used to control unstable asymptotic disturbances. For instance, the generation of Kelvin-Helmholtz vortex rings and its subsequent subharmonic instability leading to the merging of vortices in pairs, i.e., vortex pairing, 19 is a source of aeroacoustic noise which is important to control or even suppress in many industrial applications because of noise nuisance or acoustic stealth.…”
Section: Introductionmentioning
confidence: 99%
“…For larger disturbance environments other mechanisms which bypass linear growth may come into play. This process generally involves transient growth which is described by nonmodal stability theory 2,3 . The term receptivity was coined in 1969 by Morkovin 4 .…”
Section: Introductionmentioning
confidence: 99%